Maternal urinary benzophenones and infant birth size: Identifying critical windows of exposure. (March 2019) - Long, Jinlie; Xia, Wei; Li, Jiufeng; Zhou, Yanqiu; Zhao, Hongzhi; Wu, Chuansha; Liao, Jiaqiang; Jiang, Yangqian; Li, Chunhui; Li, Yuanyuan; Li, Xinping; Sun, Xiaojie; et al.
Abstract: Benzophenones (BPs) are widely used as ultraviolet absorbers and fragrance retention agents. Evidences from animal studies have suggested that exposure to BPs may affect fetal growth, but human data is limited and no study is concerning critical windows of BPs exposure throughout pregnancy in relation to fetal growth. We aimed to investigate the associations of prenatal exposure to BPs with birth size and examine the critical exposure windows of fetus development. We measured BPs (including 2, 4-dihydroxybenzophenone (BP-1), 2-hydroxy-4-methoxybenzophenone (BP-3) and 4-hydroxybenzophenone (4-OH-BP)) in maternal urine samples collected in the first, second, and third trimester from 847 mothers recruited in Wuhan, China. The general estimation equations were used to analyze the relationships between maternal exposure to BPs levels and birth size. In all newborns, we found each log unit increase in maternal urinary concentrations of BP-1 and 4-OH-BP in the 1st trimester were associated with decreases in birth length by 0.06 cm (95% confidence interval (CI): −0.11,  −0.01) and 0.08 cm (95% CI: −0.15,  −0.01), respectively, but only the association with BP-1 in the boys remained significant in the stratified analysis by infant sex. In girls, urinary concentrations of BP-1 and BP-3 in the 3rd trimester were associated with decreased birth weight (adjusted β = −27.99 g, 95% CI: −50.66,  −5.31 and −19.75 g, 95% CI: −37.31,  −2.19, respectively) and length (adjusted β = −0.08 cm, 95% CI: −0.17, 0.00 and −0.08 cm, 95% CI: −0.15,  −0.02) ( p for interaction = 0.04). Our findings indicate that maternal urinary levels of BPs in the early and late periods during pregnancy may have impacts on delayed fetal growth, and the effects were more pronounced in girls. Highlights: Urine samples were collected in three trimesters from each pregnant woman. Maternal urinary benzophenones in 1st trimester were associated with birth length. Benzophenones in early and late stages may affect fetal growth.